A severe case of brain myiasis: Treatment rationale and review of literature - Curzi, Christian; Bartoletti, Viola; Canova, Giuseppe; Giordan, Enrico (Asian Journal of Neurosurgery, 2021)
Cerebral myiasis is a rare condition caused by a parasitic infestation of fly larvae feeding on the host's necrotic or living tissue. Only 16 cases of cerebral myiasis have been published. We presented the case of a 72-year-old man with a neglected infestation of an extensive ulcerative cancer of the scalp. A large cranial lesion, with exposed brain and dura mater and severe Sarcophaga carnaria maggot infestation, was evident. We gently removed the maggots and covered the defect with thick gauze and sodium hypochlorite solution dressing. We additionally present a review of the literature to highlight shared features and suggestions for care management. In all cases, there was an absence of fatal meningitis and encephalitis, which is surprising given the open skull erosion with prolonged cortical exposure and points to the protective effects of larvae wound infestation.
Keywords: Brain; cerebral infestation; larvae; myiasis; neglected